Facing the challenges of multidrug-resistant Acinetobacter baumannii: Progress and prospects in the vaccine development - Mat Rahim, NorAziyah (Taylor & Francis, 2021)
In 2017, the World Health Organization (WHO) named A. baumannii as one of the three antibiotic-resistant bacterial species on its list of global priority pathogens in dire need of novel and effective treatment. With only polymyxin and tigecycline antibiotics left as last-resort treatments, the need for novel alternative approaches to the control of this bacterium becomes imperative. Vaccines against numerous bacteria have had impressive records in reducing the burden of the respective diseases and addressing antimicrobial resistance; as in the case of Haemophilus influenzae type b . A similar approach could be appropriate for A. baumannii. Toward this end, several potentially protective antigens against A. baumannii were identified and evaluated as vaccine antigen candidates. A licensed vaccine for the bacteria, however, is still not in sight. Here we explore and discuss challenges in vaccine development against A. baumannii and the promising approaches for improving the vaccine development process.